Quality measurement in physician-staffed emergency medical services: a systematic literature review. (15th May 2018) - Haugland, Helge; Uleberg, Oddvar; Klepstad, Pål; Krüger, Andreas; Rehn, Marius
Abstract: Purpose: Quality measurement of physician-staffed emergency medical services (P-EMS) is necessary to improve service quality. Knowledge and consensus on this topic are scarce, making quality measurement of P-EMS a high-priority research area. The aim of this review was to identify, describe and evaluate studies of quality measurement in P-EMS. Data sources: The databases of MEDLINE and Embase were searched initially, followed by a search for included article citations in Scopus. Study selection: The study eligibility criteria were: (1) articles describing the use of one quality indicator (QI) or more in P-EMS, (2) original manuscripts, (3) articles published from 1 January 1968 until 5 October 2016. The literature search identified 4699 records. 4543 were excluded after reviewing title and abstract. An additional 129 were excluded based on a full-text review. The remaining 27 papers were included in the analysis. Methodological quality was assessed using an adapted critical appraisal tool. Data extraction: The description of used QIs and methods of quality measurement was extracted. Variables describing the involved P-EMSs were extracted as well. Results of data synthesis: In the included papers, a common understanding of which QIs to use in P-EMS did not exist. Fifteen papers used only a single QI. The most widely used QIs were 'Adherence to medical protocols', 'Provision of advanced interventions', 'Response time' and 'Adverse events'. Conclusion: The review demonstrated a lack of shared understanding of which QIs to use in P-EMS. Moreover, papers using only one QI dominated the literature, thus increasing the risk of a narrow perspective in quality measurement. Future quality measurement in P-EMS should rely on a set of consensus-based QIs, ensuring a comprehensive approach to quality measurement.